Aquisição da leitura e escrita: uma análise da prática pedagógica no 2º ano do ensino fundamental - PINTO, Waldene Ferreira (2019)
The study called the ACQUISITION OF READING AND WRITING: an analysis of pedagogical practice in the second grade of elementary school aimed to investigate and observe the difficulties encountered in the process of acquisition of reading and writing skills of the students in the second grade of elementary school While intermediate step of literacy and literacy. Through a case study developed reflections concerning the learning deficit of reading and writing from the pedagogical and methodological practices observation of teachers in hurt cycle. The study conducted a literature review on the subject having re authors as Paulo Freire, Emilia Ferreiro, Ana Teberosky, Luis Carlos Cagliari, Magna Soares, among others, raising the descriptive conceptual approach that permeates the theme, In addition to the application of questionnaires with objective and subjective issues with teachers and direct observation of the performance of pupils. It was found in this conceptual path that parents have no knowledge about the importance of reading and writing in the lives of their children, as well as the teachers complain about the absence of the family at school, indicated as one of the causes of students ' difficulty in reading and writing, as well as the absence of concrete perception of the Principle that permeates the Literacy literacy Cycle represented in the first three years of elementary school. It is concluded that the difficulties in reading and writing exist, and they are present reality student school. However a participative action in integrated planning function of the pedagogical practices of teachers can contribute effectively to alleviate these difficulties, thus contributing to improving the quality of teaching.